Helicobacter pylori Activates Myosin Light-Chain Kinase To Disrupt Claudin-4 and Claudin-5 and Increase Epithelial Permeability - Fedwick, Jason P. (American Society for Microbiology, 2005)
Helicobacter pylori is a spiral, gram-negative bacterium that specifically and persistently infects the human stomach. In some individuals, H. pylori-induced chronic gastritis may progress to gastroduodenal ulcers and gastric cancer. Currently, the host-microbe interactions that determine the clinical outcome of infection are not well defined. H. pylori strains capable of disrupting the gastric epithelial barrier may increase the likelihood of developing serious disease. In this study, H. pylori strain SS1 increased gastric, but not small intestinal, permeability in C57BL/6 mice. H. pylori strain SS1 was able to directly increase paracellular permeability, in the absence of host inflammatory cells, by disrupting the tight-junctional proteins occludin, claudin-4, and claudin-5 in confluent nontransformed epithelial cells. H. pylori SS1 also reduced claudin-4 protein levels in human gastric AGS cells. The ability of H. pylori SS1 to increase permeability appeared to be independent of the well-characterized virulence factors vacuolating cytotoxin and CagA protein. H. pylori activated myosin light-chain kinase in epithelial cells to phosphorylate myosin light chain and increase permeability by disrupting claudin-4 and claudin-5. The bacterial factor responsible for increasing epithelial permeability was heat sensitive, membrane bound, and required apical contact with monolayers. In conclusion, disruptions of the tight junctions observed in this study implicate host cell signaling pathways, including the phosphorylation of myosin light chain and the regulation of tight-junctional proteins claudin-4 and claudin-5, in the pathogenesis of H. pylori infection.